Steam pretreatment to improve enzymatic saccharification of oil palm Elaeis guineensis empty fruit bunch - Shamsudin, Saleha (2013)
An abundant production of oil palm empty fruit bunch (EFB) from palm oil mill has created environmental issues to the surrounding localities primarily due to the inefficient disposal and incineration. Nevertheless, lignocellulosic EFB has a great potential as renewable feedstock. In addition, suitable pretreatment for EFB also have to be considered for commercial exploitation. Besides that, the conversion of EFB into biofuels and chemicals is one of the most feasible conversion route strategy in terms of sustainability compared to fossil fuel. Steam pretreatment has been chosen as a favourable pretreatment of EFB to be implemented in the palm oil mill due to the availability of steam being continuously generated as part of the mill’s operation and the excess steam. In this study, we investigate the potential of using steam at 140°C from the palm oil mill back-pressure vessel as pretreatment for EFB. Major alterations occurred in the morphology of EFB as observed under the scanning electron microscope. The highest total conversion of 30% based on amount of pretreated EFB into sugar by Celluclast 1.5-L from Trichoderma reesei was achieved. In order to increase the EFB biomass conversion to sugars, higher pressure of saturated steam pretreatment was then studied using 500 cm3 reactor of steam pretreatment unit, whereby EFB is subjected to different saturated steam temperatures (130-230°C) for 2 to 8 minutes. The pretreated EFB concentration of 2% (w/v) with Acremonium cellulase was used in all saccharification experiments. As expected, the high pressure steam pretreatment can increase the digestibility by enzymatic hydrolysis of EFB. Using an excess of cellulase from Acremonium cellulolyticus demonstrated the greatly enhanced xylose (216.3 g kg-1 steam pretreated EFB) and glucose (621 g kg-1 steam pretreated EFB) digestibility by steam pretreatment at 140°C and 210°C, respectively. The results were compared by ANOVA and Turkey multiple range test using SPSS. The highest glucose achieved was 0.927 g glucose g-1 cellulose. The quantitative (BET) and the qualitative (FTIR/XRD/TG) analysis verified the effectiveness of steam pretreated EFB as a reactive substrate for biomass conversion via enzymatic hydrolysis system. Increased of EFB’s surface area by fragmentation and development of cracks had enhanced the conversion of holocellulose, especially xylan into xylose, which is the second most important sugars of biomass. Higher pressure of saturated steam is necessary to modify the major parts of EFB, including the changes of inter/intra hydrogen bonding, biomass crystallinity and thermal stability behavior, which attributed to the removal of substantial hemicellulose part and enhanced the cellulose-lignin mixtures for high glucose production. From this study, a two-step steam pretreatment of EFB for the direct separation of xylose and glucose by enzymatic saccharification is proposed; 140°C for high yield of xylose and 210°C for high yield of glucose as lowcost substrates for biofuels and biomaterials production. Various chemical products could be generated from hemicellulose degradation at 210°C such as furfural (147.2 g kg-1 EFB), organic acids (39.1 g kg-1 EFB) and monosaccharides (66.9 g kg-1 EFB) from steam pretreatment of EFB which accounted for 91.4% of solubilized hemicellulose substances. The detail results of mass balance were well described and the energy consumption for saturated steam pretreatment at 210°C (32.8 MJ/kg) and 140°C (13.5 MJ/kg) from the 500 cm3 steam pretreatment unit operation werees timated. Based on the energy excess found in the palm oil mill, the energy use to pretreat EFB for subsequent high xylose (140°C) and glucose production (210°C) were enough to be implemented in the palm oil mill. After steam pretreatment and saccharification, the calorific values of EFB residues were upgraded into solid product with favorable solid fuel characteristics (16.3 to 19.7 MJ/kg with 1–5 wt% moisture content).